Constructing a Universal Ruler: Sultan Mehmet II and Hybrid Legitimacies of the Ottoman Empire - Hasbi, Baiquni; Angkasa, Muhammad Akbar (International Journal of Islamic Khazanah, 2025)
This study revisits the complex imperial identity of Ottoman Sultan Mehmed II (Muhammad al-Fatih), to challenge the conventional portrayal of his reign as exclusively Islamic. While modern Muslim communities in Indonesia and Turkiye celebrate him as an ideal Islamic hero, a closer reading of historical sources reveals a ruler whose legitimacy emerged from a deliberate synthesis of Islamic, Byzantine, and Persian traditions—an identity best described as Islamicate. Through a critical examination of Tursun Beg’s Tarih-i Ebü’l-Feth, this study demonstrates how Intellectuals strategically wove together sacred, political and aesthetic symbols to construct Mehmed II’s authority as a universal ruler rather than a merely Muslim conqueror. By unsettling the binary of Islamic versus Christian civilizations, this study situates Mehmet II within a broader, polycentric Islamicate world and highlights the continuing relevance of his hybrid legitimacy for rethinking pluralism and political identity in contemporary Muslim societies.